How to motivate your team to perform - Burghgraef, Rich. (Cranbrook : Global Professional, 2011)
The latest theories on management are presented, analyzed and recommended. An important theme throughout the book is the importance of planning and of listening closely and empathizing with your staff in order to promote good will and prevent misunderstanding.
oif 15/09/14
Loan
Keywords: Employee motivation; Employees; Performance; Organizational effectiveness; Organizational behavior